(untitled) (Research, Society and Development, 2020)
Education experiences a time when the combination of small adjustments in the cultural ways of learning and teaching are no longer sufficient to face the challenges of the new generations, who are immersed in a new technological reality. Unfortunately, this reality is not assimilated by many teachers who still have difficulties and resistance in the application of these technologies in the classroom. This article has the aim to present the results of research on the acceptance and use of digital technologies by teachers and students in initial teacher training courses at the University of Coimbra, in Portugal. The methodological proposal involved the documentary analysis of teaching programs; meeting with coordinators and application of a questionnaire to teachers and students of the course. The results point to teachers and students, future teachers, aware of the potential of the technologies, using them as preparation in the teaching activities. However, the fact that they use digital technology does not guarantee that they will make the pedagogical use of technologies with students.